COMPETENCE APPROACH TO ORGANIZATION OF EXTRACURRICULAR ACTIVITIES AT THE UNIVERSITY - Semen P. Bashkirov; Olga A. Volkova (Moscow Polytechnic University, 2016)
The article analyzes formation of the axiological competences in the educational environment of higher educational institution. These competences characterize the youth's need in constructive activity. The authors present the experience of USTU in the implementation of the competence approach to the formation of youth personnel reserve by means of the student construction team movement.